Child Crime As Perpetrators Of Immoral Crimes - Zulfikar Kamarmir; Junifer Dame Panjaitan (Worldwide Research Publishing, 2023)
This research delves into the criminal responsibility of children engaged in moral crimes, specifically focusing on decency crimes like rape within the framework of Indonesia's legal system, as outlined in